Internalization of Sufism Values in Learning Moral Beliefs in Madrasah Aliyah - Samdani, Samdani; Syafruddin, Rif'an; Tamjidnor, Tamjidnor; Syafqy Abda, Muhammad (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The moral crisis and the rise of materialism among students indicate a gap in Islamic education, particularly in shaping spiritual character. This study aims to examine the internalization of Sufi (tasawuf) values in the teaching of Aqidah Akhlak at Madrasah Aliyah Normal Islam Putera Rasyidiyah Khalidiyah Amuntai. Using a qualitative approach with a case study method, data were collected through in-depth interviews, direct observations, and analysis of learning documents. The findings reveal that Sufi values such as sincerity (ikhlas), patience (sabar), trust in God (tawakal), and detachment from materialism (zuhud) are effectively integrated through reflective learning, teacher role modeling, and the strengthening of the school’s spiritual culture. The internalization process primarily occurs through the hidden curriculum, which is manifested in daily routines and the school's religious atmosphere, rather than through formal instruction. This study highlights the transformative potential of the Sufi approach in shaping students’ moral and spiritual character holistically. Through the application of Sufi values, the madrasah serves not only as an educational institution but also as a spiritual training ground that fosters self-awareness, sincerity, and closeness to Allah SWT within students.